Volunteering and the strategic value of ignorance - Florian Morath (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2010)
Private provision of public goods often takes place as a war of attrition: individuals wait until someone else volunteers and provides the good. After a certain time period, however, one individual may be randomly selected. If the individuals are uncertain about their cost of provision, but can find out about this cost ahead of the volunteering game, a strategic value is attached to the information, and individuals may prefer not to learn their cost of provision. If the time horizon is sufficiently short, in equilibrium only one individual may acquire information about his cost. For a long time horizon, acquiring information is strictly dominant. The time limit is an important instrument in influencing the efficiency of the volunteering game. – – Die private Bereitstellung öffentlicher Güter ähnelt häufig einem Zermürbungskrieg: Die Beteiligten warten, bis sich jemand anderes freiwillig meldet und das öffentliche Gut bereitstellt. Nach einer gewissen Zeitperiode des Wartens kann jedoch ein Beteiligter zufällig dazu bestimmt werden, die Bereitstellung zu übernehmen. Wenn die Beteiligten ihre Bereitstellungskosten nicht genau kennen, sich aber vor dem Bereitstellungsspiel Information über ihre Kosten beschaffen können, dann kommt dieser Information ein strategischer Wert zu; die Beteiligten könnten es vorziehen, ihre Bereitstellungskosten nicht genau zu kennen. Wenn der Zeithorizont des Bereitstellungsspiels hinreichend kurz ist, entscheidet sich im Gleichgewicht lediglich ein Beteiligter, Information zu akquirieren. Bei einem längeren Zeithorizont ist es eine strikt dominante Strategie, sich Information zu beschaffen. Der Zeithorizont stellt ein wichtiges Instrument zur Beeinflussung der Effizienz des Bereitstellungsspiels dar.
Keywords: H41; D44; D82; D83; 330; War of attrition; volunteering; discrete public goods; asymmetric information; information acquisition